2010
DOI: 10.3354/ab00215
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of whale shark Rhincodon typus aggregations near South Ari Atoll, Maldives Archipelago

Abstract: We made surveys for whale sharks Rhincodon typus on a total of 99 d from April through June each year from 2006 to 2008 along the southern fringe of the South Ari Atoll, Maldives Archipelago. We recorded the length and sex of each shark observed and made photographs to facilitate repeated identification from their spot patterns using pattern-recognition software. We identified 64 whale sharks from digital photographs taken during 220 sightings over 3 yr. Approx. 87% of those sharks were immature males. The ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 40 publications
4
70
1
4
Order By: Relevance
“…There was significant male bias (87%) for those individuals whose sex could be confirmed, though it could not be determined for 62.5% of individuals. Such male bias is consistent with coastal aggregations from across the globe Rowat et al, 2007Rowat et al, , 2009Riley et al, 2010;Ramírez-Macías et al, 2012a,b;Himawan et al, 2015;Rohner et al, 2015b) and with others from within the Philippines (Araujo et al, 2014. Adult-dominated sites remain a rarity, namely at Darwin's Arch in the Galapagos Islands (ECU), Gorda Banks in Baja California (MEX), at an offshore aggregation in Qatar (QAT), and at St Helena Island (GBR) in the South Atlantic, and at a newly identified area in the mid-equatorial Atlantic off Brazil (Ramírez-Macías et al, 2012b;Acuña-Marrero et al, 2014;Clingham et al, 2016;Macena and Hazin, 2016;Robinson et al, 2016).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…There was significant male bias (87%) for those individuals whose sex could be confirmed, though it could not be determined for 62.5% of individuals. Such male bias is consistent with coastal aggregations from across the globe Rowat et al, 2007Rowat et al, , 2009Riley et al, 2010;Ramírez-Macías et al, 2012a,b;Himawan et al, 2015;Rohner et al, 2015b) and with others from within the Philippines (Araujo et al, 2014. Adult-dominated sites remain a rarity, namely at Darwin's Arch in the Galapagos Islands (ECU), Gorda Banks in Baja California (MEX), at an offshore aggregation in Qatar (QAT), and at St Helena Island (GBR) in the South Atlantic, and at a newly identified area in the mid-equatorial Atlantic off Brazil (Ramírez-Macías et al, 2012b;Acuña-Marrero et al, 2014;Clingham et al, 2016;Macena and Hazin, 2016;Robinson et al, 2016).…”
Section: Discussionsupporting
confidence: 54%
“…The population estimate at Donsol of 1,767 ± 41 is comparable to estimates from the Gulf of Mexico of 2,167 individuals (McKinney et al, 2017), although different methods were applied. It is considerably larger though than estimates from Ningaloo with 320-440 individuals , the Seychelles with 348-488 individuals (Rowat et al, 2009), the Maldives with 68-81 individuals (Riley et al, 2010) or Holbox Island, Mexico, with 521-809 individuals (Ramírez-Macías et al, 2012a) using the same methods. Although markrecapture approaches provide an estimate of population size, these numbers are more indicative than absolute, particularly in light of a lack of standardized methods for estimating whale shark abundance across sites.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the Maldives, 63 individuals were identified (95% immature males) with a mean length of 5.9 m AE 1.5 m s.d. (Riley et al 2010), while in Mozambique 300 individuals (81% males) were identified with a mean length of 6.7 m (Pierce et al 2008). By comparison, the Djibouti aggregation, while similar in sex ratio to these other aggregation areas with 85% males to 15% females, had a much smaller mean length than whales sharks in any other aggregations (3.7 m AE 0.6 m s.d.).…”
Section: Length Ranges and Sex Ratiosmentioning
confidence: 99%
“…Most information on these sharks comes from studies conducted in coastal areas where the sharks are known to aggregate on a regular basis and where the majority of sharks have been found to be juveniles or sub-adults (,8 m), such as at Ningaloo Reef, Western Australia (Meekan et al 2006), the Maldives (Anderson and Ahmed 1993;Riley et al 2010), northern Mexico (Eckert and Stewart 2001) and the Philippines (Alava et al 1997) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%